A correlation of the structure and chemical composition of the habitat sediments with the ecological flow of Acheloos river in Trikala Prefecture, Thessaly, Greece. - Evelpidou, N.; Dimitriou, E.; Papadaki, Ch.; Stamatakis, M.; Ntoanidis, L.; Koutsomichou, I.; Anastasatou, M.; Karkani, A. (10th International Congress of the Hellenic Geographical Society, 2014)
During the implementation of fieldwork for the “Ecoflow” Cooperation project, in Acheloos River, Trikala Prefecture, Central Greece, 10 unstructured sediment samples were extracted from 3 sites along the river banks for measurements and analysis. The samples were taken from the areas of Drosochori (DR 1, DR 2 & DR 3), Aspropotamos (ASP 1 & ASP 3) and Mesochora (KOR 1, KOR 2, MES 1, MES 2, & MES 4). For granulometric analysis of the samples, the Folk &Ward method (2222) was used. As it was resulted, all samples are classified as gravelly sands to sandy gravels, poorly to very poorly sorted, very coarse to very fine skewed and platykurtic to mesokurtic. The ΧRD mineralogical analysis showed that in all the samples quartz is the major component. Calcite or dolomite [one sample] content is ranging between major through medium values. The presence of the magnesian calcite, which was found in two samples, is most likely attributed to biological sources (i.e. epiphytes, shells, etc), as commonly occur white colonies of small coral-like assemblages stack on the permanently wet pebbles observed close to the river banks. Sodium feldspars predominantly albite] are present in half of the samples as medium component and as trace component in the other half. By contrast, potassium feldspars [mainly orthoclase] are always present in minor/trace amounts. The presence of clay minerals, when considered as a group, is that of a medium or minor component. As the clay minerals content increases, the water has more suspended particles, so the river's turbidity during stormy events is strongly influenced. The higher content of clay minerals in the samples of Mesochora (downstream) indicates a different source of sediment from that of the other samples. By comparing the mineralogical analysis results with river water chemical analysis results from the same sampling sites, it becomes evident that the analyzed sediments do not provide the river waters with ions, as can be deduced from the low content of alkalies and alkaline earth metals. Sulphates and chlorides were detected in trace amounts in the water samples, whereas no sulphate minerals or halides there were detected in the sediments analysed. It is therefore concluded that there is not any buried evsaporite source in the vicinity of the sampling areas. In addition, the significantly low content of nitrates, nitrites and ammonia demonstrate the nonexistent contamination from biogenic factors. Another factor that plays a crucial role in the ecological status of the river is the availability of sediment for the development and maintenance of suitable habitats for the icthyofauna. The composition and structure of sediments affect their transportation and deposition behaviour which impacts the substrate of the river habitats. To assess this aspect in the study area, habitat suitability curves for specific fish species have been used that describe the best substrate for the necessary river habitats to support the breeding and reproduction of the particular fish species. The representation of the sample sediments in the substrate types required has been estimated by combining the results from habitat mapping, suitability curves and the sediment analyses. The results indicated that the type of material available in the particular river segments is appropriate for the maintenance and development of the habitat types that are required for a good ecological status.